The Long Term Financial Sustainability Of The Civil Service Pension Scheme In Malaysia - Darmaraj, Sheila Rose (2017)
CSPS is a non-contributory and a defined-benefit pension scheme for all government employees who are eligible for pension. Under this scheme, the employees do not contribute for their pension and all expenditure is borne by the government through tax revenues. With the growing number of public sector employees, their longer life expectancy, and the expanding benefits under the CSPS, spending on pensions has been escalating. The main objective of the study was to assess its financial sustainability in terms of the pension deficit (ratio of pension deficit to total wages) and financial gap (pension deficit as a percentage of GDP). A country specific model that allows the projections of future expenditures and revenues over a period of 75 years was used to undertake this exercise under eight alternative scenarios.